Identity, nomenclature and distribution of some rare flowering plants of Orissa and its adjoining states in India. - Panda, P. C.; Das, P. (Rheedea, 1997)
Nomenclature and distribution of Aglaia haslettiana Haines, Weihea ceylanica (Gardn.) Baill., lndochloa clarkei (Hack.) Bor, Lasiococca comberi Haines, Mucuna minima Haines, Tragia gagei Haines, Pomatocalpa decipiens (Lindi.) J.J. Sm., Cedrela brevipetiolulata Haines and Uvaria eucincta Bedd. ex Dunn which are rare and so far considered as endemic to Orissa and the adjoining states of Andhra Pradesh, Madhya Pradesh and Bihar have been discussed.